Increasing acceptance of a vaccination program for coronavirus disease 2019 in France: A challenge for one of the world's most vaccine-hesitant countries. Issue 2 (21st January 2022) - Cambon, L.; Schwarzinger, M.; Alla, F.
Highlights: The French people are among the most reluctant to be vaccinated against Covid_19. The crisis management is partly responsible for this hesitancy. We identified the mechanisms allowing to overcome this hesitancy. Four strategies triggering these mechanisms are presented in a model. Abstract: France is one of the most vaccine-hesitant countries in the world, including for coronavirus disease 2019 (COVID-19). After 10 months of restrictive measures and media coverage of the dangers of COVID-19, French attitudes towards a vaccine continue to deteriorate. The communication strategies of the government have not helped; in fact, they have made the situation worse. Empirical studies on the national strategy for management of the COVID-19 pandemic in France have shed light on the reasons for vaccine hesitancy. These studies have identified four pillars for the vaccination strategy: i) Communication regarding the importance of herd immunity, ii) making healthcare workers the focus of the vaccination campaign, iii) citizen mobilization and guaranteed consultations, and iv) access to free vaccines without delay. This paper discusses the evidence supporting this strategy.